INCREASING STUDENTS' MOTIVATION AND ENGAGEMENT THROUGH A TECHNOLOGY-ENHANCED LEARNING ENVIRONMENT (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article investigates strategies for enhancing students’ learning motivation and fostering active engagement in the educational process through the implementation of a Technology-Supported Learning Environment (TSLE) in higher education institutions.The paper analyzes the impact of digital tools, distance learning platforms, and interactive technologies on students’ psychology, as well as their role in improving educational effectiveness. The results of the study demonstrate that integrating technology with pedagogical approaches is a key factor in stabilizing and sustaining student motivation.